THE EFFECT OF FINANCIAL PERFORMANCE ON THE HUMAN DEVELOPMENT INDEX MODERATED ECONOMIC GROWTH IN REGENCY/CITY IN THE PROVINCE OF RIAU ISLAND - Azwandi, Azwandi; Wibisono, Chablullah; Gita Indrawan, M.; Satriawan, Bambang; Khaddafi, Muammar (RADJA PUBLIKA, 2022)
The results of this study indicate that the Independence Ratio has a significant positive effect on the Human Development Index. The Fiscal Decentralization Ratio has a significant positive effect on the Human Development Index, the PAD Effectiveness Ratio has a significant positive effect on the Human Development Index, the Independence Ratio has a significant positive effect on Economic Growth, the Fiscal Decentralization Ratio has a significant positive effect on Economic Growth, the PAD Effectiveness Ratio has a significant positive effect on Economic Growth , the Independence Ratio has a positive and insignificant effect on the Human Development Index moderated by Economic Growth, the Fiscal Decentralization Ratio has a significant positive effect on the Human Development Index moderated by Economic Growth.